A Computational Model of Task Overload Management and Task Switching. (September 2013) - Wickens, Christopher D.; Santamaria, Amy; Sebok, Angelia
We describe a computational model that predicts the decision aspect of sequential multitasking. We investigate how people choose to switch tasks or continue performing an ongoing task when they are in overload conditions where concurrent performance of tasks is impossible. The model is based on a metaanalytic integration of 46 experiments from two literatures: interruption management and applied task switching. Consistent trends from the meta-analysis are used to set parameters in the mathematical model, which is then implemented in a task network model.